Properties and Utilisation of Tropical Bamboo (Gigantochloa Scortechinii), for Structural Plywood - Uyup, Mohd Khairul Anwar (2003)
The objectives of these study were to determine the physical and mechanical properties of 4-year-old Gigantochloa scortechinii culms and to evaluate the properties of plywood manufactured from the bamboo culms. Bamboo culms were split using hand splitter to produce splits. Strips were prepared by removing the epidermis and the inner skin using knife, whereas outer splits were prepared by removing the inner skin of the culm. For the bamboo plywood production, the bamboo strips were glued edge-to-edge using polyvinyl acetate resin into a 410 mm x 410 mm x 4 mm sized laminate. The laminates were then bonded perpendicularly to each other using phenol formaldehyde resin to produce tbreeply bamboo plywood. The assembly time was set at 30 min and bamboo plywood was consolidated by hot pressing at 140°C and pressure of 14 kg'cm2 for 6.5 minutes. Commercial structural plywood (Grade A) Merawan species with the same thickness as the bamboo plywood (12 mm) was used for comparison purposes. The results of the physical studies indicate that within the culm wall, the moisture content decreased from the interior towards the peripheral layer of the culm while the specific gravity increased. The moisture content decreased with height, whilst specific gravity increased. In the strip form, bamboo shrank: more in both radial and tangential directions than in the longitudinal direction. Between radial and tangential, shrinkage occurs more in radial than in tangential. The mean value of modulus of rupture (MOR) for the bamboo strips (179.6 N/mm2) showed no significant difference with splits (periphery layer oriented upward, 158.3 N/mm2) but a significant difference was observed when compared with the periphery layer oriented downwards (134.2 N/mm2).